PENGARUH PARTISIPASI ANGGARAN TERHADAP SENJANGAN ANGGARAN PEMERINTAH DAERAH DENGAN GAYA KEPEMIMPINAN, KARAKTER PERSONAL, KAPASITAS INDIVIDU, DAN KOMITMEN ORGANISASI SEBAGAI VARIABEL MODERATING (Survei pada SKPD Kabupaten Kampar) - Muhammad Dzaky; M. Rasuli '; Alfiati Silfi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
This study aim to examine the influence of budgetary participation to budgetary slack with Leadership Style, Personal Characteristics, Individual Capacity and Organizational Commitmenas Moderating Variables as moderated variables at (Survey in SKPD Kampar). The data was collected by distributing questionnaires with purposive sampling to the respondents. While responders is consisted by the functional functionary aselon III and IV at governmental institution of Kampar which is participation in budgetary process, with a total sample are 84 respondents. The method analisys used in this study is multiple regression analysis with software SPSS for windows. From the results of multiple regression, there is five hypothesis that influent to budgetary slack : 1) the effect of budgetary participation having an effect on budgetary slack. 2) budgetary participation and Leadership Style interaction have significant influence to the budgetary slack. 3) budgetary participation and Personal Characteristics interaction have significant influence to budgetary slack. 4) Individual Capcity failed as moderate the relationship between budgetary participation and budgetary slack. 5) budgetary participation and Organizational Commitment interaction have significant influence to budgetary slack.Keywords : Budgetary Slack, Leadership Style, Personal Characteristics, Individual Capacity, Organizational Commitment.